2009
DOI: 10.1002/tea.20284
|View full text |Cite
|
Sign up to set email alerts
|

Science teachers' perceptions of the school environment: Gender differences

Abstract: Because the school environment has been shown to play an important role in teacher and student performance, we undertook research into the assessment of school environment, differences between female and male science teachers' perceptions of their school environments, and associations between these school environment perceptions and teachers' background characteristics. Although gender differences in science education have attracted both public concern and academic interest, little research has specifically ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
4
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 55 publications
1
27
4
5
Order By: Relevance
“…However, the qualitative results show a much more complex picture; domineering and cooperative strategies are used by both, male and female participants (Tanaka, 2009). In another study conducted among science teachers from secondary schools in Taiwan, it was found that female science teachers perceived greater collegiality among teachers, higher gender equity among students, and stronger professional interest, and male science teachers perceived lower work pressure and better teacher-student relations (Huang & Fraser, 2009). Also, in a study conducted in the three Netherlands schools, it was discovered that female students in the mixed gender groups did not learn to solve physics problems as well as male partners or as female students in all-female dyads.…”
Section: Studies Done In Other Countriesmentioning
confidence: 99%
“…However, the qualitative results show a much more complex picture; domineering and cooperative strategies are used by both, male and female participants (Tanaka, 2009). In another study conducted among science teachers from secondary schools in Taiwan, it was found that female science teachers perceived greater collegiality among teachers, higher gender equity among students, and stronger professional interest, and male science teachers perceived lower work pressure and better teacher-student relations (Huang & Fraser, 2009). Also, in a study conducted in the three Netherlands schools, it was discovered that female students in the mixed gender groups did not learn to solve physics problems as well as male partners or as female students in all-female dyads.…”
Section: Studies Done In Other Countriesmentioning
confidence: 99%
“…This may be due to women's emphasis on emotional connection at work. Male science teachers, on the other hand perceived lower work pressure and better teacher-student relations (Huang & Fraser, 2009), probably due to men's emphasis on solving problems, and moving on.…”
Section: Studies Done In Other Countriesmentioning
confidence: 99%
“…Teachers' understandings of a child will in turn affect the child's learning. Research has also shown that teachers' presumptions and expectations of a child are important for the children's performances in science subjects (Huang and Fraser 2009;Kahle and Meece 1994;She and Fisher 2002). Although teachers, when questioned, say that they have the same expectations for girls' and boys' achievements in science, their teaching practises do suggest the opposite (Kahle et al 1991;Kahle and Meece 1994).…”
Section: Teachers' Understandings Of Science Students and Gendermentioning
confidence: 99%